Characterization, genome analysis and genetic tractability studies of a new nanocellulose producing Komagataeibacter intermedius isolate - Pietro Cannazza; Antti J. Rissanen; Essi Sarlin; Dieval Guizelini; Carlotta Minardi; Pauli Losoi; Francesco Molinari; Diego Romano; Rahul Mangayil (Scientific Reports, 2022)
Abstract Bacterial nanocellulose (BC) is a highly versatile biopolymer currently pursued as a material of choice in varied themes of biomedical and material science research fields. With the aim to extend the biotechnological applications, the genetic tractability of the BC producers within the Komagataeibacter genus and its potential as an alternative host chassis in synthetic biology have been extensively studied. However, such studies have been largely focused on the model Komagataeibacter spp. Here, we present a novel K. intermedius strain capable of utilizing glucose, and glycerol sources for biomass and BC synthesis. Genome assembly identified one bacterial cellulose synthetase (bcs) operon containing the complete gene set encoding the BC biogenesis machinery (bcsI) and three additional copies (bcsII–IV). Investigations on the genetic tractability confirmed plasmid transformation, propagation of vectors with pBBR1 and p15A origin of replications and constitutive and inducible induction of recombinant protein in K. intermedius ENS15. This study provides the first report on the genetic tractability of K. intermedius, serving as starting point towards future genetic engineering of this strain.